PENGARUH KEBIJAKAN DIVIDEN, KEBIJAKAN HUTANG DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN PERBANKAN YANG LISTING DI BURSA EFEK INDONESIA) - Rosita, Rosita; Mas’ud, Arifuddin; Ruslan, Ruslan (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2024)
This research aims to determine the effect of dividend policy, debt policy and profitability on company value (study empirical on banking companies that listed on the indonesia stock exchange). The type of data used is quantitative data. The data source used is secondary data. The sampling method used with purposive sampling . The analytical tool used in panel data linear regression is Eviews version 13. The research results simultaneously show that the Dividend Policy, Debt Policy and Profitability variables have an influence on Company Value. Meanwhile, in the partial test, the dividend policy variable has an effect on company value, while debt and profitability policy has no effect on company value in banking institutions listed on the Indonesian Stock Exchange.This means that when Dividend Policy, Debt Policy, and Profitability are improved, the Company's Value also tends to increase. The research that states this hypothesis supports that these three variables do play an important role in determining the value of the company.